Navigating Sino-Thai 'rocky' bilateral ties: The geopolitics of riverine trade in the Greater Mekong Subregion. (August 2020) - Lin, Shaun; Grundy-Warr, Carl
The revived plan to dynamite rapids and rocky islets in Chiang Rai province of Thailand as part of an Upper Mekong navigation improvement scheme allowing bigger tonnage Chinese cargo ships to pass more smoothly all the way to Luang Prabang in Laos has been folded into the wider visions of BRI. These rework and invert a geopolitical imaginary that has imperial origins in the Lower Mekong, when the French sought to navigate upstream from Indochina during 19th century explorations. Our paper examines the rock-blasting plans and shifting responses from and relations between Laos and Thailand in light of past and contemporary geopolitical narratives.